Pengaruh Komunikasi Kerja, Kepuasan Kerja, dan Komitmen Organisasional terhadap Kinerja Karyawan pada Divisi Quality Control (QC) PT Sanipak Indonesia - Edy Kurniawan; Sumardin Sumardin; Mulyadi Mulyadi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses issues related to ineffective vertical communication, perceived inequality in compensation, and low organizational commitment among employees in the Quality Control division of PT Sanipak Indonesia. The objective of this research is to examine the effect of work communication, job satisfaction, and organizational commitment on employee performance, both partially and simultaneously. A quantitative approach with a survey method was employed, involving 45 employees selected using a saturated sampling technique. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression. The findings indicate that job satisfaction and organizational commitment have a positive and significant effect on employee performance, while work communication shows a positive but not statistically significant effect when analyzed simultaneously. Furthermore, the three variables collectively have a significant impact on performance, explaining 84.60% of its variance. Among them, organizational commitment emerges as the most influential factor. These results suggest that strengthening employee commitment and ensuring fair and supportive work conditions are essential strategies to improve performance, supported by effective organizational communication practices.